2006
DOI: 10.1007/s00122-006-0391-2
|View full text |Cite
|
Sign up to set email alerts
|

Tall fescue genomic SSR markers: development and transferability across multiple grass species

Abstract: Simple sequence repeat (SSR) markers are highly informative and widely used for genetic and breeding studies. Currently, a very limited number of SSR markers are available for tall fescue (Festuca arundinacea Schreb.) and other forage grass species. A tall fescue genomic library enriched in (GA/CT)( n ) repeats was used to develop primer pairs (PPs) flanking SSRs and assess PP functionality across different forage, cereal, and turf grass species. A total of 511 PPs were developed and assessed for their utility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
86
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(96 citation statements)
references
References 45 publications
8
86
1
1
Order By: Relevance
“…It has been reported that EST-SSR markers show lower polymorphism compared to genomic SSR markers (Saha et al, 2006). In our research, a total of 9 EST-SSR markers have been found polymorphic from 49 EST-SSRs, giving a polymorphism rate of 18%, compared with the 72% polymorphism rate found by Burstin et al (2001).…”
Section: Discussionmentioning
confidence: 53%
“…It has been reported that EST-SSR markers show lower polymorphism compared to genomic SSR markers (Saha et al, 2006). In our research, a total of 9 EST-SSR markers have been found polymorphic from 49 EST-SSRs, giving a polymorphism rate of 18%, compared with the 72% polymorphism rate found by Burstin et al (2001).…”
Section: Discussionmentioning
confidence: 53%
“…The PCR products were analyzed with ABI 3730 DNA Analyzer (Applied Biosystems) following the protocol suggested by Saha et al [31]. ABI data were scored as present (1) or absent (0) with GeneMapper Software v 3.7.…”
Section: Genotyping and Sequencingmentioning
confidence: 99%
“…Moreover, due to their association with coding sequences, EST-SSRs can also lead to the direct gene tagging for QTL mapping of agronomically important traits and increase the efficiency of marker-assisted selection [15]. In addition, EST-SSRs show a higher level of transferability to closely related species than genomic SSR markers [13,16-18] and can be served as anchor markers for comparative mapping and evolutionary studies [19,20]. …”
Section: Introductionmentioning
confidence: 99%